ADME gene polymorphisms do not influence the pharmacokinetics of docetaxel: Results from a population pharmacokinetic study in Indian cancer patients. (22nd June 2021) - Patil, Anand; Shriyan, Bharati; Mehta, Parsshava; Patil, Mrudula; Gurjar, Murari; Nookala, Manjunath; Patil, Vijay; Joshi, Amit; Noronha, Vanita; Prabhash, Kumar; Gota, Vikram
Abstract: Background: Pharmacokinetics (PK) of docetaxel is characterized by high inter‐individual variability (IIV). While covariate models that explain the PK variability of docetaxel exist, not much is known about the effects of genetic variations on docetaxel disposition. Methods: Fifty patients with head and neck or prostate cancer were enrolled of whom two patients withdrew consent before the start of the study. Docetaxel was administered at either 50 or 75 mg/m 2 as intravenous infusion over 1 h. One pharmacogenetic sample and a series of PK samples, either intensive ( N  = 5; 13 samples each) or sparse ( N  = 43; 6 samples each), were collected from each patient. Docetaxel levels were estimated using a validated HPLC method. Polymorphic loci on the Absorption, Distribution, Metabolism, and Elimination (ADME) genes were identified using the PharmacoScan array platform. Population pharmacokinetic analysis was carried out using NONMEM v7.2. Results: Docetaxel PK was well characterized by a three‐compartment model. Clearance (Cl) was found to be 18 L/h with an IIV of 45.3%. None of the genetic variants showed significant covariate effect on the Cl of docetaxel. Patients with abnormal alanine aminotransferase (ALT) were found to have 25% lower Cl as compared to patients with normal ALT values. However, the covariate effect could not be established in the final model possibly due to lack of adequate number of patients with abnormal ALT. Conclusion: Genetic polymorphisms in the ADME gene do not explain the IIV in PK of docetaxel. However, patients with abnormal liver function might require dose reduction. Clinical trial registration: Not applicable since participants in this study received treatment that was standard of care. Abstract : The study aims to explain the inter‐individual variability in the pharmacokinetics of docetaxel using a population pharmacokinetic approach. Our results conclusively exclude pharmacogenetic variants as a significant covariate, while recommending dose modification for patients with hepatic impairment.